Accessing the biocompatibility of layered double hydroxide by intramuscular implantation: histological and microcirculation evaluation - Cunha, Vanessa Roberta Rodrigues (Sci Rep, 2016)
Biocompatibility of layered double hydroxides (LDHs), also known as hydrotalcite-like materials or double metal hydroxides, was investigated by in vivo assays via intramuscular tablets implantation in rat abdominal wall. The tablets were composed by chloride ions intercalated into LDH of magnesium/aluminum (Mg(2)Al-Cl) and zinc/aluminum (Zn(2)Al-Cl). The antigenicity and tissue integration capacity of LDHs were assessed histologically after 7 and 28 days post-implantation. No fibrous capsule nearby the LDH was noticed for both materials as well any sign of inflammatory reactions. Sidestream Dark Field imaging, used to monitor in real time the microcirculation in tissues, revealed overall integrity of the microcirculatory network neighboring the tablets, with no blood flow obstruction, bleeding and/or increasing of leukocyte endothelial adhesion. After 28 days Mg(2)Al-Cl promoted multiple collagen invaginations (mostly collagen type-I) among its fragments while Zn(2)Al-Cl induced predominantly collagen type–III. This work supports previous results in the literature about LDHs compatibility with living matter, endorsing them as functional materials for biomedical applications.